Effect of bore fluid on reverse osmosis hollow fiber membranes - 561615 Ani Idris; Noordin Mohd. Yusof; Scientific Conference of the Electron Microscopy Society Malaysia (12th : 2003 : Langkawi, Kedah) (Skudai : Universiti Teknologi Malaysia, 2003)
50